Analisis Keterlibatan Orang Tua dalam Mendukung Pembelajaran Fiqih Anak Usia Sekolah Dasar - Tauhid, Moh. (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
Elementary school age is the first foundation in the formal education process for children, where teaching fiqh is one of the main pillars in forming their religious understanding. However, the fiqh learning process does not only occur in the school environment but is also influenced by factors outside the school, especially the role of parents. This research aims to analyze the fiqh learning materials for elementary school-aged children, the contribution of parents in supporting elementary school-aged children's fiqh learning, as well as the problem of involving parents in elementary school-aged children's fiqh learning. The method used in this research is the library research method. The results of the research show that fiqh learning material for elementary school-age children includes ablution material, prayer material, fasting material, and Islamic morals and ethics material. Parents' contributions include providing an example, teaching Islamic values, involving children in religious practices, encouraging discussions and questions, and providing emotional support. Meanwhile, the problems involving parents in learning fiqh for elementary school-age children include limited religious knowledge, busyness and time, lack of resources, disinterest or other priorities, and ignorance of the importance of the role of parents. It is hoped that this research can provide a better understanding of the role of parents in forming children's understanding of religion at an early age, as well as provide input for schools and parents in increasing effective collaboration to support children's Islamic jurisprudence learning in elementary schools.